Accounting of the magnetic field of the power supply system of a power-capacitive technical object - A. T. Tarlanov; Z. M. Kurbanismailov (Российский технологический журнал)
The paper shows the approach and the result of taking into account the mutual influence of on-board subsystems of a complex technical object along the DC power supply circuits. Technical objects are understood as a mobile, energy-intensive vehicle, such as an aircraft, a surface or submarine vessel, or a railway locomotive with strong magnetic fields. The aim of the work is to create a simple and intuitive tool for mathematical modeling of the magnetic field vector at an arbitrarily specified observation point. The task is being solved in order to improve the accuracy of magnetic measurements on board, in particular, in navigation problems. On-board DC networks are considered, to which the approach of mathematical modeling is applied. The disadvantages of commercial programs of a similar purpose are noted. The binding of the objects under consideration to the general coordinate system is described. An analytical algorithm for calculating the magnetic field vector from the on-board cable network with a pronounced 3D trajectory is shown. Examples of visualization of the simulation results are given. An algorithm for calculating the induction vector based on the Biot-Savard law is considered. The algorithm for the analytical solution of the problem is described in detail. A specific power cable of the on-board network is considered. The cable is given by a set of straight conductors with current. The ways of future improvement of the created product with the transition from one observation point to the field map in a given three-dimensional zone of arbitrary position, volume and orientation are outlined. The obtained result is considered as an element of the procedure for achieving electromagnetic compatibility of energy-intensive and highly sensitive subsystems of a modern complex technical object.